Effect of Morphine-Sensitization in D2 Receptor Gene Expression in the Mice Brain in the Absence and Presence of Lithium Chloride - Hoda Mehregan; Majid Sadeghizadeh; Mohammad Reza Zarrindast; Kayhan Azadmanesh; Ali Jahanshahi; Hadi Shirzad; Mojtaba Saadati (Cell Journal, 2010)
Objective: In this study we have investigated the changes in D2 receptor expression levelin morphine-sensitized mice, in the absence and presence of lithium chloride (LiCl). Theresult would pave the way to comprehend and confront this complicated event.Materials and Methods: Male NMRI mice, weighing 20-25g, were used in this study.They were divided into six groups. The first group received 0.9% saline as the controlgroup and the other group was treated with morphine sulphate (30 mg/kg). LiCl (5 and 10mg/kg treatments) was separately performed in two other groups. The final two groupswere simultaneously treated with morphine sulphate (30 mg/kg) and LiCl (5 mg/kg) inone group and morphine sulphate (30 mg/kg) accompanied by LiCl (10 mg/kg) in theother group. All injections were performed intraperitoneally and once daily. After a fiveday wash-out, mice were decapitated and the brain regions which included the striatum,prefrontal cortex (PFC) and hippocampus were extracted. Using relative Real-Timepolymerase chain reaction (PCR), the expression levels of the long (D2L) and short (D2S)isoforms of the D2 receptor were investigated.Results: Morphine treatment leads to a significant increase (p<0.0.5) in D2S levels in thestriatum and PFC but has no effect on D2L levels in the examined regions. In the groupreceiving LiCl 5mg/kg, the D2L levels showed a significant augmentation in PFC and thehippocampus (p<0.05) as well as the striatum (p<0.001). The D2S levels in the samegroup, significantly increased in the PFC (p<0.05) and striatum (p<0.001). LiCl at a doseof 10 mg/kg did not alter the expression of either isoforms in any region. While simultaneousadministration of morphine and LiCl (10 mg/kg) resulted in a marked increase in D2Slevels in the striatum (p<0.001) and PFC (p<0.05), morphine administration along withLiCl (5mg/kg) was ineffective on the expression levels of D2L and D2S isoforms whencompared to the control group.Conclusion: Morphine sensitization leads to an increase in D2S receptor expressionand is affected by lithium in a dose-dependent manner where the lower dose inhibits andhigher dose to enhances this effect. It is assumed that sensitization-induced changes inthe transcript level are more regulated by dopamine transmission rather than by the directeffect of morphine and/or lithium on gene expression.